2017
DOI: 10.31018/jans.v9i2.1276
|View full text |Cite
|
Sign up to set email alerts
|

Effect of foliar application of potassium and its spray schedule on yield and yield parameters of sweet orange (Citrus sinensis Osbeck) cv. Jaffa

Abstract: An investigation to evaluate the effect of foliar application of potassium and its spray schedule on yield and yield parameters in sweet orange cv. Jaffa was undertaken at experimental orchard, Department of Horticulture, CCS Haryana Agricultural University, Hisar during the year 2014-15. The results revealed that the foliar application of potassium nitrate at the rate of 2 and 4 % and potassium sulphate at 1.5 and 3.0 % significantly improved average fruit weight, fruit diameter, percentage of medium and larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…One study [31] revealed that all used treatments, including foliar application with potassium citrate, were effective in increasing the yield of 'Canino' apricot trees when compared with control. Furthermore, [32] indicated that the foliar application of potassium nitrate and potassium sulphate significantly enhanced the yield of 'Jaffa' sweet oranges over the control (water spray). Moreover, the fruit yield of plum trees was improved by foliar application of potassium nitrate as compared to the control [33].…”
Section: Fruit Yieldmentioning
confidence: 99%
“…One study [31] revealed that all used treatments, including foliar application with potassium citrate, were effective in increasing the yield of 'Canino' apricot trees when compared with control. Furthermore, [32] indicated that the foliar application of potassium nitrate and potassium sulphate significantly enhanced the yield of 'Jaffa' sweet oranges over the control (water spray). Moreover, the fruit yield of plum trees was improved by foliar application of potassium nitrate as compared to the control [33].…”
Section: Fruit Yieldmentioning
confidence: 99%
“…Also, it was found that average fruit weight, fruit diameter, medium and large fruits%, and tree bearing of sweet orange cv. Jaffa was enhanced significantly above untreated trees when treated with Potassium sulphate at 1.5 and 3.0 % (Vijay et al ., 2017). Taha et al ., (2014) noted that high increment in the bear tree, fruit set %, average fruit weight and diminished of proportions of fruit drop are committed by the exogenous foliar spray of potassium sulphate and humic acid independently or by mixing the two materials.…”
Section: Discussionmentioning
confidence: 99%
“…Our results may gain support from those obtained by Arquero et al (2006), Sarrwy et al (2010), Hussein (2008), Abdel-Nasser and EL-Shazly (2001), Amnon et al (2018/2019) on olive trees. Moreover, (Vijay et al, 2017) found that foliar application of potassium nitrate and potassium sulphate significantly enhanced the yield of 'Jaffa' sweet oranges and potassium nitrate improved fruit yield of plum trees (Jawandha et al, 2017). On 'Canino' apricot trees, the yield was increased significantly with the application of potassium citrate (Haggag et al, 2016) and application of potassium nitrate and potassium citrate (Okba et al, 2021).…”
Section: Fruit Set and Yieldmentioning
confidence: 99%
“…Mineral nutrition is one of the main tools for improving fruit yield and quality ( Tagliavini and Marangoni, 2002). It is well known that spraying fruit trees with nutrients improved vegetative growth, flowering and correction of deficiency symptoms reflects on the quality of the fruits (Josan et al, 1995 andDalal et al, 2017).…”
Section: Introductionmentioning
confidence: 99%